Examining the influence of hydration status on physiological responses and running speed during trail running in the heat with controlled exercise intensity - Lopez, R. M.; Casa, D. J.; Jensen, K. A.; DeMartini, J. K.; Pagnotta, K. D.; Ruiz, R. C.; Roti, M. W.; Stearns, R. L.; Armstrong, L. E.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to determine the effects of dehydration at a controlled relative intensity on physiological responses and trail running speed. Using a randomized, controlled crossover design in a field setting, 14 male and female competitive, endurance runners aged 30 ± 10.4 years completed 2 (hydrated [HY] and dehydrated [DHY]) submaximal trail runs in a warm environment. For each trial, the subjects ran 3 laps (4 km per lap) on trails with 4-minute rests between laps. The DHY were fluid restricted 22 hours before the trial and during the run. The HY arrived euhydrated and were given water during rest breaks. The subjects ran at a moderate pace matched between trials by providing pacing feedback via heart rate (HR) throughout the second trial. Gastrointestinal temperature (TGI), HR, running time, and ratings of perceived exertion (RPE) were monitored. Percent body mass (BM) losses were significantly greater for DHY pretrial (-1.65 ± 1.34%) than for HY (-0.03 ± 1.28%; p < 0.001). Posttrial, DHY BM losses (-3.64 ± 1.33%) were higher than those for HY (-1.38 ± 1.43%; p < 0.001). A significant main effect of TGI (p = 0.009) was found with DHY having higher TGI postrun (DHY: 39.09 ± 0.45°C, HY: 38.71 ± 0.45°C; p = 0.030), 10 minutes post (DHY: 38.85 ± 0.48°C, HY: 38.46 ± 0.46°C; p = 0.009) and 30 minutes post (DHY: 38.18 ± 0.41°C, HY: 37.60 ± 0.25°C; p = 0.000). The DHY had slower run times after lap 2 (p = 0.019) and lap 3 (p = 0.025). The DHY subjects completed the 12-km run 99 seconds slower than the HY (p = 0.027) subjects did. The RPE in DHY was slightly higher than that in HY immediately postrun (p = 0.055). Controlling relative intensity in hypohydrated runners resulted in slower run times, greater perceived effort, and elevated TGI, which is clinically meaningful for athletes using HR as a gauge for exercise effort and performance.